Time and cost study on cold-formed steel and reinforced concrete construction - a comparison - Hu, Wei Kiet (Universiti Malaysia Sarawak, UNIMAS, 2008)
Nowadays, the usage of cold-formed steel is quite common in some developed countries especially in building construction. However, in Malaysia, cold-formed steel construction is still considered as a new construction method. In local construction industry, cold-formed steel is only commonly seen in roof truss construction. In traditional construction method, reinforced concrete construction is still greatly favoured by local construction industry. The aim of this research is to study the potential use of cold-formed steel in Malaysian construction industry as compared with traditional construction method, reinforced concrete construction. A comparison was done with 2 principles of project management criteria for a successful project, time and cost. An interview was conducted with consulting engineers, contractors, developers, material suppliers and architects on the market reactions towards cold-formed steel. This research was conducted based on real life reinforced concrete structure project in Sarawak. Based on the practice of low-cost housing project, the time to complete the project and the total cost for the project were estimated based on experience of site engineers.